Strategies Of Akidah Akhlak Teachers in Preventing Bullying Behavior Against Students at Madrasah Tsanawiyah Soleh Al-Mubarok, Tanjung Jabung Barat - Riska Ameliya; Khoirul Anwar (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The persistence of bullying in educational settings reflects a critical disjunction between formal moral instruction and students’ lived social practices, a challenge increasingly recognized across global education systems. This study aims to investigate the structural patterns of bullying behavior and to analyze the preventive strategies employed by Akidah Akhlak teachers within an Islamic junior secondary school context. A qualitative case study design was employed, involving one principal, two teachers, and twelve students selected through purposive sampling, with data collected via semi-structured interviews, participatory observation, and document analysis, and analyzed using triangulation and thematic analysis to ensure analytical rigor. The findings reveal that bullying is socially reproduced through normalized peer interactions, with verbal aggression emerging as the most dominant and persistent form. The study identifies an integrated set of teacher strategies, including moral exemplification, contextual Quranic value internalization, restorative discipline, and collaborative learning, which collectively function as a preventive system fostering moral awareness, emotional regulation, and prosocial behavior. However, the effectiveness of these strategies is constrained by external influences, particularly family environment and digital media exposure, which introduce competing value systems beyond the school context. This study offers a novel contribution by advancing an integrated Islamic-based framework that bridges moral pedagogy with socio-emotional and contextual dimensions of student interaction, thereby moving beyond fragmented approaches to bullying prevention. Positioned within the global educational discourse, the proposed framework provides a comprehensive and context-sensitive model for addressing complex social challenges, while offering practical insights for educators and policymakers in designing sustainable anti-bullying interventions across diverse educational settings.